Corporate cash holdings and firm life cycle: evidence from China. Issue 4 (26th May 2021) - Rehman, Ajid Ur; Ahmad, Tanveer; Hussain, Shahzad; Hassan, Shoaib
Abstract : Purpose: The purpose of this paper is to investigate how corporate cash holdings changes across firm life cycle and how firms undergo heterogeneous dynamic cash adjustment as they advance from one stage to the next stage. Design/methodology/approach: This study uses an extensive data set of 2, 994 Chinese A-listed firms. The authors use generalized method of moments (GMM) and Fisher Panel unit root testing to investigate the targeting behavior of Chinese firms. Findings: The uni-variate investigation reveals that firms in the growth stage exhibits the highest cash levels and firms in the decline stage report the lowest cash levels. As growth firms have high investment needs, they may require raising external capital to meet investment needs. To avoid the costly external financing, firms in growth stage tend to hold more cash. The GMM estimation reveals that along all the phases of firm life cycle there are evidences of trade-off behavior of corporate cash holdings. The authors report that adjustment rate increases as firms enters into the growth stage. Practical implications: The findings provide both theoretical and practical insight to align cash policies with the available strategic choices along firm life cycle in an emerging market characterized by market imperfections. Originality/value: The study is unique from the context that it is applying robust methodology to one of rarely investigated area in corporate cash policy. The peculiar Chinese study setting characterized by higher information asymmetry, high cost of external financing and heterogeneous access to financing sources provide theoretical and empirical underpinnings to investigate and gain insight about how corporate cash policy can be aligned with strategic choices available across different stages of life cycle.